Troubleshooting Windows 7 - Halsey, Mike (O'Reilly Media, 2012)
"In this webcast Mike Halsey MVP, the author of Troubleshooting Windows 7 Inside Out, will show you some of the ways you can maximise productivity by using clever troubleshooting techniques."--Resource description page.